Cover Image, Volume 9, Issue 5. (16th August 2017) - Ozcelikkale, Altug; Moon, Hye‐ran; Linnes, Michael; Han, Bumsoo
Abstract : The cover image, by Altug Ozcelikkale et al., is based on the Advanced Review In vitro microfluidic models of tumor microenvironment to screen transport of drugs and nanoparticles, DOI: 10.1002/wnan.1460 . Abstract : The cover image, by Altug Ozcelikkale et al., is based on the Advanced Review In vitro microfluidic models of tumor microenvironment to screen transport of drugs and nanoparticles, DOI: 10.1002/wnan.1460 .